Enhancement of solubility of albendazole by complexation with β-cyclodextrin - Moriwaki,C. (2008)
A high dosage of albendazole (ABZ) is required for treating systemic helminthe infections because of its low solubility. Aiming at increasing ABZ solubility, complexation with beta-cyclodextrin (β-CD) using aqueous and acetic acid solutions as ABZ solubilizer was studied. In aqueous β-CD, complexation increased solubility 53.4 times, giving a complex equilibrium constant of 1266 L mol-1 with a maximum ABZ concentration of 276 µmol L-1 for 16.3 mmol L-1 β-CD. For complexation in 1.05 mol L-1 acetic acid, UV absorbance spectra and ¹H-NMR analysis confirmed complex formation. The UV absorbance of ABZ/acid acetic/β-CD solutions was modeled by the formation of two complexes with molar ratios 1:1 and 1:2 ABZ:β-CD. When neutralized with NaOH these solutions did not form precipitates only for the ABZ:β-CD molar ratios of 1:8 and 1:10, showing that ABZ solubility could be increased 306 times. Results show that high β-CD molar ratios hold ABZ in solution by complexation enhanced by the acetate anion.